Interactome of Site-Specifically Acetylated Linker Histone H1 - Höllmüller, Eva; Greiner, Katharina; Kienle, Simon Maria; Scheffner, Martin; Marx, Andreas; Stengel, Florian (My University, 2021)
Linker histone H1 plays a key role in chromatin organization and maintenance, yet our knowledge of the regulation of H1 functions by post-translational modifications is rather limited. In this study, we report on the generation of site-specifically mono- and di-acetylated linker histone H1.2 by genetic code expansion. We used these modified histones to identify and characterize the acetylation-dependent cellular interactome of H1.2 by affinity purification mass spectrometry and show that site-specific acetylation results in overlapping but distinct groups of interacting partners. Among these, we find multiple translational initiation factors and transcriptional regulators such as the NAD+-dependent deacetylase SIRT1, which we demonstrate to act on acetylated H1.2. Taken together, our data suggest that site-specific acetylation of H1.2 plays a role in modulating protein–protein interactions.
Keywords: 570